Implicatures in discourse : the case of Spanish NP anaphora - Blackwell, Sarah E. (Pragmatics & beyond ;, 2003)
Implicatures in Discourse examines Spanish conversations and oral narratives in order to seek support for a pragmatic theory of anaphora. Blackwell argues that the use of anaphoric expressions may be considered conversational implicatures that give rise to inferences of coreference and non-coreference. Her analysis shows how speakers abide by Levinson's 'neo-Gricean' principles of Quantity, Informativeness, and Manner, but that grammatical, semantic, cognitive, and pragmatic constraints interact with the neo-Gricean principles, influencing anaphora use and interpretation. The study also reveal.